Effectiveness of the graded motor imagery to improve hand function in patients with distal radius fracture: A randomized controlled trial - Dilek, Burcu; Ayhan, Çiğdem; Yağcı, Gözde; Yakut, Yavuz (Hanley & Belfus-Elsevier Inc, 2018)
Study Design: Single-blinded randomized controlled trial. Introduction: Pain management is essential in the early stages of the rehabilitation of distal radius fractures (DRFx). Pain intensity at the acute stage is considered important for determining the individual recovery process, given that higher pain intensity and persistent pain duration negatively affect the function and cortical activity of pain response. Graded motor imagery (GMI) and its components are recent pain management strategies, established on a neuroscience basis. Purpose of the study: To investigate the effectiveness of GMI in hand function in patients with DRFx. Methods: Thirty-six participants were randomly allocated to either GMI (n = 17; 52.59 [9.8] years) or control (n = 19; 47.16 [10.5] years) groups. The GMI group received imagery treatment in addition to traditional rehabilitation, and the control group received traditional rehabilitation for 8 weeks. The assessments included pain at rest and during activity using the visual analog scale, wrist and forearm active range of motion (ROM) with universal goniometer, grip strength with the hydraulic dynamometer (Jamar; Bolingbrook, IL), and upper extremity functional status using the Disability of the Arm, Shoulder and Hand Questionnaire, and the Michigan Hand Questionnaire. Assessments were performed twice at baseline and at the end of the eighth week. Results: The GMI group showed greater improvement in pain intensity (during rest, 2.24; activity, 6.18 points), wrist ROM (flexion, -40.59; extension, -45.59; radial deviation, -25.59; and ulnar deviation, -26.77 points) and forearm ROM (supination, -43.82 points), and functional status (Disability of the Arm, Shoulder and Hand Questionnaire, 38.00; Michigan Hand Questionnaire, -32.53 points) when compared with the control group (for all, P < .05). Conclusion: The cortical model of pathological pain suggests new strategies established on a neuroscience basis. These strategies aim to normalize the cortical proprioceptive representation and reduce pain. One of these recent strategies, GMI appears to provide beneficial effects to control pain, improve grip strength, and increase upper extremity functions in patients with DRFx.
WOS: 000426227500002
PubMed ID: 29122370
Keywords: Radius Fractures; Rehabilitation; Pain; Graded Motor Imagery